2011
DOI: 10.1007/s10734-011-9476-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-explanation in the domain of statistics: an expertise reversal effect

Abstract: This study investigated the effects of four instructional methods on cognitive load, propositional knowledge, and conceptual understanding of statistics, for low prior knowledge students and for high prior knowledge students. The instructional methods were (1) a reading-only control condition, (2) answering open-ended questions, (3) answering open-ended questions and formulating arguments, and (4) studying worked-out examples of the type of arguments students in the third group had to formulate themselves. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 31 publications
0
30
0
1
Order By: Relevance
“…The benefits of backward‐fading, however, may diminish as students develop more domain expertise because of the redundancy of viewing completed and partially completed problems once the steps needed to solve a particular type of problem are understood (Kalyuga, Chandler, Tuovinen, & Sweller, ). Evidence of the expertise reversal effect suggests that for statistical problem‐solving in particular (which is the focus of the present study), studying example problems is more helpful for students with low prior knowledge than for students with high prior knowledge and strategies such as self‐explanation and formulating arguments may be more beneficial for those with high prior knowledge (Leppink, Broers, Imbos, van der Vleuten, & Berger, ).…”
Section: Introductionmentioning
confidence: 83%
“…The benefits of backward‐fading, however, may diminish as students develop more domain expertise because of the redundancy of viewing completed and partially completed problems once the steps needed to solve a particular type of problem are understood (Kalyuga, Chandler, Tuovinen, & Sweller, ). Evidence of the expertise reversal effect suggests that for statistical problem‐solving in particular (which is the focus of the present study), studying example problems is more helpful for students with low prior knowledge than for students with high prior knowledge and strategies such as self‐explanation and formulating arguments may be more beneficial for those with high prior knowledge (Leppink, Broers, Imbos, van der Vleuten, & Berger, ).…”
Section: Introductionmentioning
confidence: 83%
“…This method of first having students answer open-ended questions that can then help them to evaluate more complex hypotheses is also called the method of propositional manipulation (Broers, 2002(Broers, , 2009. Although this method was originally developed for and examined within the context of individual learning (Broers, 2002;Leppink et al, 2011Leppink et al, , 2012a, it has also been applied in pair learning (Leppink et al, 2012b) and lecture learning (Leppink, 2012) contexts.…”
Section: Methodsmentioning
confidence: 99%
“…This finding, also known as the expertise reversal effect, was also demonstrated in the domain of statistics (Leppink, 2011(Leppink, , 2012. Two randomized experiments (Leppink, Broers, Imbos, Van der Vleuten, & Berger, 2012a, 2012b demonstrated that students who have limited prior knowledge learn more from the study of fully or partially worked examples than from autonomous performance of learning tasks. Furthermore, one of the experiments (Leppink et al, 2012a) indicated that novice students who in their study restrict themselves to merely reading a study text perform better rather than worse than students who study the same text with guiding questions.…”
Section: The Influence Of Students' Prior Knowledgementioning
confidence: 99%
See 2 more Smart Citations